KUALITAS PELAYANAN DALAM PEMBANGUNAN INFRASTRUKTUR DI KECAMATAN CIAWI, KABUPATEN BOGOR - Muhamad Alfian; Nandang Saefudin Zenju; Irma Purnamasari (LPPM Universitas Djuanda Bogor, 2018)
Infrastructure development is an integral part of national development and the driving wheel of economic growth. Infrastructure also has an important role in strengthening national unity and unity (Bappenas: 2009). The banjarwaru, banjarwangi, and telukpinang highways are the access roads traversed by 8 villages including alternative routes for the cicurug-sukabumi area. This road is always passed by the people who headed to the city. Therefore, the benefits of this road is very important because it is often passed from the cicurug-sukabumi area due to the diversion of traffic flow so that the intensity of high road users.In this study the author uses the theory of Ridwan and Sudrajat. Quality of service is the level of incompatibility between expectations with customer desires and also the perceptions of these customers. Quality of service here can be assessed by looking at the dimensions. These dimensions include the quality of service, the ability of officials, and service convenience. During the observation to the community through the survey to direct approach with the community, most people complained that the development service to build the kecamatan should be further improved and the results of this study showed that the Quality Assessment of Service in Road Infrastructure Development in Ciawi Sub-district Bogor Regency is categorized Fair Good this is because the assessment of the quality of development services by the Subdistrict Apparatus itself and from the community assess the ability of District Officers still have to be improved in conducting the service and its implementation.Keywords: Service Quality, Infrastructure Development.